Determining the Potential Roles of Branched-Chain Amino Acids in the Regulation of Muscle Growth in Common Carp (Cyprinus carpio) Based on Transcriptome and MicroRNA Sequencing - Xianglin Cao; Han Cui; Xinyu Ji; Baohua Li; Ronghua Lu; Yuru Zhang; Jianjun Chen (Aquaculture Nutrition)
Branched-chain amino acids (BCAAs) can be critically involved in skeletal muscle growth and body energy homeostasis. Skeletal muscle growth is a complex process; some muscle-specific microRNAs (miRNAs) are involved in the regulation of muscle thickening and muscle mass. Additionally, the regulatory network between miRNA and messenger RNA (mRNA) in the modulation of the role of BCAAs on skeletal muscle growth in fish has not been studied. In this study, common carp was starved for 14 days, followed by a 14-day gavage therapy with BCAAs, to investigate some of the miRNAs and genes that contribute to the regulation of normal growth and maintenance of skeletal muscle in response to short-term BCAA starvation stress. Subsequently, the transcriptome and small RNAome sequencing of carp skeletal muscle were performed. A total of 43,414 known and 1,112 novel genes were identified, in addition to 142 known and 654 novel miRNAs targeting 22,008 and 33,824 targets, respectively. Based on their expression profiles, 2,146 differentially expressed genes (DEGs) and 84 differentially expressed miRNA (DEMs) were evaluated. Kyoto Encyclopedia of Genes and Genome pathways, including the proteasome, phagosome, autophagy in animals, proteasome activator complex, and ubiquitin-dependent protein catabolic process, were enriched for these DEGs and DEMs. Our findings revealed the role of atg5, map1lc3c, ctsl, cdc53, psma6, psme2, myl9, and mylk in skeletal muscle growth, protein synthesis, and catabolic metabolism. Furthermore, miR-135c, miR-192, miR-194, and miR-203a may play key roles in maintaining the normal activities of the organism by regulating genes related to muscle growth, protein synthesis, and catabolism. This study on transcriptome and miRNA reveals the potential molecular mechanisms underlying the regulation of muscle protein deposition and provides new insights into genetic engineering techniques to improve common carp muscle development.